2013
DOI: 10.1210/en.2012-2234
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and Bone: Macrophage-Derived TSH-β Splice Variant Increases Murine Osteoblastogenesis

Abstract: It is now firmly established that TSH may influence the physiology and patho-physiology of bone by activating osteoblasts and inhibiting osteoclast activity resulting in relative osteoprotection. Whether this influence is directly exerted by pituitary-derived TSH in vivo is less certain, because we have previously reported that the suppression of pituitary TSH does not remove such protection. Here, we have characterized the functional relevance of a novel form of the TSH-β subunit, designated TSH-βv, known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…Macrophages were also found to express D2 (Kwakkel et al 2014), TRα1 and possibly also TRβ although authors have reported conflicting results (Billon et al 2014, Kwakkel et al 2014, Lourbopoulos et al 2014, Perrotta et al 2014. Several recent papers have demonstrated that both human and murine macrophages are able to produce a functional TSHβ splice variant that is positively regulated by T 3 and capable of stimulating the TSH receptor (Vincent et al 2009, Baliram et al 2013, 2016. It has been suggested that this TSHβ splice variant plays a role in bone physiology; however, whether it affects macrophage function is currently unknown.…”
Section: Intracellular Thyroid Hormone Metabolism In Macrophagesmentioning
confidence: 99%
“…Macrophages were also found to express D2 (Kwakkel et al 2014), TRα1 and possibly also TRβ although authors have reported conflicting results (Billon et al 2014, Kwakkel et al 2014, Lourbopoulos et al 2014, Perrotta et al 2014. Several recent papers have demonstrated that both human and murine macrophages are able to produce a functional TSHβ splice variant that is positively regulated by T 3 and capable of stimulating the TSH receptor (Vincent et al 2009, Baliram et al 2013, 2016. It has been suggested that this TSHβ splice variant plays a role in bone physiology; however, whether it affects macrophage function is currently unknown.…”
Section: Intracellular Thyroid Hormone Metabolism In Macrophagesmentioning
confidence: 99%
“…Studies using ex vivo bone marrow cell cultures show that TSH inhibits and stimulates TNFα production from macrophages and osteoblasts, respectively [76]. TNFα, in turn, not only stimulates osteoclastogenesis but also enhances the production in bone marrow of a variant TSHβ [76,77]. This locally produced TSH suppresses osteoclast formation in a negative feedback loop.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…7,8 Since then not only has every pituitary hormone, namely FSH, TSH, growth hormone, adenocorticotrophic hormone (ACTH), and prolactin, as well as posterior pituitary neuropeptides, oxytocin and vasopressin, been shown to act directly on bone, but also that certain of these hormones are produced by bone cells to exert potential autocrine and paracrine actions. [7][8][9][10][32][33][34][35][36][37][38][39] [41][42][43][44][45][46][47][48] The bone loss has been attributed solely to estrogen deficiency since the time Fuller Albright described post-menopausal osteoporosis. 49 However, a more careful look at the SWAN data indicates that the most rapid rates of bone loss occur~3 years prior to the onset of the last menstrual period.…”
Section: Interdisciplinary Effort To Re-purpose Bisphosphonates Formentioning
confidence: 99%